1980
DOI: 10.1115/1.3254767
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dynamic Programming to Optimize Tool Replacement Schedules for Multi-Tool Operations Involving Distributed Tool Lives

Abstract: There have been a number of models developed to provide the optimum tool replacement schedule for a multi-tool set-up. However, most of these models are quite complex and are geared to yield solutions for a very large set-up involving an indefinite number of parts. In this paper a new tool replacement model aimed at a machining process involving a moderate number of tools (2 to 6) and a discrete number of parts (50 to 100) is developed based on the technique of Dynamic Programming. Tool lives in the set-up are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, studies adopting a more unified approach towards all aspects of tool management have recently started appearing in the literature. Stecke (1983Stecke ( , 1989; Stecke and Talbot (1985); Kusiak (1986a); Sarin and Chen (1987);Cuppan (1986); Ventura et al (1988) Bao (1980Kordysh (1987); Sharit andElhence (1989) Crite et al (1985); Maccarini et al (1987); Perera and Carrie (1987);Hedlund et al (1990) Rutelli andCuppini (1988); Kincaid (1989);Powell et al (1984); Gee et al (1984);Brown (1988); Stockline (1984 and) Knutton (1990);Quinlan (1988b); Kochan (1986); Murphy and Kay (1987); Ames (1986);Brigida (1986) Brunette (1989; Bellmann and Becker (1989) Mason (1986Gayman (1987) …”
Section: Tool Management Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies adopting a more unified approach towards all aspects of tool management have recently started appearing in the literature. Stecke (1983Stecke ( , 1989; Stecke and Talbot (1985); Kusiak (1986a); Sarin and Chen (1987);Cuppan (1986); Ventura et al (1988) Bao (1980Kordysh (1987); Sharit andElhence (1989) Crite et al (1985); Maccarini et al (1987); Perera and Carrie (1987);Hedlund et al (1990) Rutelli andCuppini (1988); Kincaid (1989);Powell et al (1984); Gee et al (1984);Brown (1988); Stockline (1984 and) Knutton (1990);Quinlan (1988b); Kochan (1986); Murphy and Kay (1987); Ames (1986);Brigida (1986) Brunette (1989; Bellmann and Becker (1989) Mason (1986Gayman (1987) …”
Section: Tool Management Researchmentioning
confidence: 99%
“…Bao (1980) has developed a dynamic programming formulation to optimize tool replacement schedules under a specified set of machining parameters. In his formulation, four options for tool replacement are considered at each stage: (1) replace no tools, (2) replace a particular tool, (3) replace a group of tools, and (4) replace all tools.…”
Section: Tool Replenishmentmentioning
confidence: 99%
“…A thorough review of the solution methodologies related to tool replacement can be found in McCullough [5], Armarego and Brown [6], Pa'sko [7], Batra and Barash [8], Bao [9], LaCommare et al [10], Sharit and Elhence [11], Zhou et al [12] and Tak [13]. As has been mentioned by Zhou et al [12], the various authors have classified tool replacement strategies in different ways.…”
Section: Studies On Tool Replacementmentioning
confidence: 99%
“…A complete Tool Replacement Strategy specifies a tool change schedule based upon the economic service lives of tools and a control policy regarding unscheduled tool changes following breakage. The most realistic replacement strategies have considered the distributed nature of tool lives under actual machining parameters, as well as the option to change several tools once one fails [9,10], rather than considering only expected lives and single tool replacement [5,6]. All of these tool replacement studies have considered one machine in isolation.…”
Section: Studies On Tool Replacementmentioning
confidence: 99%
“…Bao [18] proposed a dynamic programming model for a tool replacement policy in a multi-tool environment. The author used log-normal, Weibull, and gamma probability functions to represent actual tool life distributions.…”
Section: Tool Life Distributionsmentioning
confidence: 99%